Applicability and Cost Implication of Labor-Based Methods for Sustainable Road Maintenance (SRM) in Developing Countries - Berhane Grum; Dejene Tsegaye; Zeru Tariku; Dmtsu Gebremariam; Haftom Gebremicael; Taamrat Kuhilen; Shishay Yemane; Ashenafi Aregawi; Bizuneh A. Abebe (Advances in Civil Engineering)
Regular maintenance keeps roads in a good working condition for users. Road maintenance can be conducted using labor and machine based methods. In this study, applicability and costs of labor-based, namely employment intensive (EI), labor intensive (LI), and labor-based equipment-supported (LBES) road maintenance methods were investigated with a case study in Tigray region, northern Ethiopia. The objectives of this study were therefore to (a) identify road defects and outline the corresponding labor-based maintenance methods, (b) compare relative costs of the three labor-based road maintenance methods, and (c) explore indicators of sustainable road maintenance (SRM) practices for developing countries. The results of this study showed that the labor-based methods are suitable for maintaining a wide range of road defects such as pavement cracks, bleeding, potholes, and rutting. Results of the cost analysis revealed that the LI and EI were 6% and 36% cheaper than the LBES method for repairing shoulder damage in asphalt roads. Roadside bush clearing using LBES resulted in 40% and 147% cost saving compared to EI and LI methods, respectively. Average share of labor cost compared to combined cost of labor and equipment in EI, LI, and LBES was 97%, 79%, and 37%, respectively. Unit rates of maintenance activities for different labor-based methods were also developed for Tigray region. The developed road maintenance unit rates will be useful for estimating cost of labor-based methods in Tigray and other similar regions in Ethiopia. In this study, 45 suitability indicators under 10 categories and three themes (social, economic, and environmental) were developed to improve future road maintenance practices in developing countries. Finally, it is recommended to use SRM practices to increase sustainability of road infrastructure in developing countries.